PENGARUH LITERASI KEUANGAN, PERENCANAAN KEUANGAN, PERILAKU KEUANGAN, DAN INKLUSI KEUANGAN TERHADAP KESEJAHTERAAN KEUANGAN PELAKU UMKM DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - ,Aunurrrafiq, Ifan Ariza , Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Financial literacy is financial knowledge and capability that affects efforts to improve financial well-being (Hidayah et al., 2021). This study aims to examine and analyze the effect of financial literacy, financial planning, financial behavior, and financial inclusion on financial well-being. This research includes quantitative research. The total population in this study was 1,384 SMEs in the district. High Cliffs, Meranti Islands Regency. The sampling method used in this study is non-probability sampling with the side quota method. This research was collected through a survey by distributing questionnaires, where the respondents consisted of SMEs in the district. Tebing Tinggi, Meranti Islands Regency, which is in the trade, service provider, and food/beverage processing sector with a total of 200 respondents. The data were analyzed using multiple regression method using SPSS version 26. The results of the study prove that financial literacy, financial planning, financial behavior, and financial inclusion on financial welfare. Keywords: Financial Literacy, Financial Planning, Financial Behavior, Financial Inclusion, and Financial Welfare.